Alternate Rapid Maxillary Expansion and Constriction (Alt-RAMEC) protocol: A Comprehensive Literature Review - skelMuhammed Hilmi Büyükçavuş (Galenos Yayinevi, 2019)
The aim of this comprehensive review is to introduce clinicians to the increasingly popularity Alt-RAMEC procedure, a method commonly used in the treatment of class III malocclusion in the last 15 years. Another application of the literature to enhance the skeletal effects of Class III treatment on the maxillae is the Alternative Rapid Maxillary Expansion and Constriction (Alt-RAMEC) procedure introduced by Liou, which improves the effectiveness of the maxillae relative to the surrounding sutures and the enhancement of the maxillae. In the Alt-RAMEC protocol, maxillae will be enlarged to be 1 mm per day, first enlarged to 7 mm, and then the 1 mm screw is closed. In other weeks, in this order the screw of the expansion device is turned on for one week and then closed for one week, completing the Alt-RAMEC protocol at the end of the 9-week process. In this review, we will discuss the advantages and disadvantages of the studies, which include successful treatments by applying this protocol, differences with other methods, its effect on the airway, and its advantages and disadvantages.